Hysterical Blokes and the Other's Jouissance. Issue 2 (8th October 2014) - Dickson, Andrew; Kerfoot, Deborah; Knights, David; Sabelis, Ida
<x xml:space="preserve">Abstract</x> This paper represents an attempt to theorize the feminine writing of organization through the Lacanian logic of sexuation. It also represents an attempt by a man to practise the feminine writing of organization. Using autoethnographic methods, I attempt to reformulate the 'female' problem of weight anxiety through the eyes of a weight anxious man and thus to provide a radical (re)thinking of gender. By linking a man's experience of weight anxiety to Lacan's hysteric's discourse, I demonstrate how men can experience the Other's jouissance and find themselves 'on the feminine side'. I then use this logic to argue that the feminine writing of organization is an attempt to harness the Other's jouissance, as author to place oneself as the object of the Other's desire, in other words to become hysterical.